Femvertising As an Important Trend in The Internet Communication - Paulina GAJEWSKA; Irena SZEWCZYK (Communications of International Proceedings, 2022)
In recent times, there was a belief that instant messaging and social media would be used mainly as an opportunity to communicate with other people, and their primary task would be to provide entertainment to users. However, nowadays, due to their dynamic development and spreading popularity, it can be noticed that they have become the so-called social media trend. Social media have turned into sources of information that provide a large dose of knowledge, as well as become opinion-forming portals where people can share opinions on a variety of topics. For this reason, social media began to play one of the main roles of strengthening and promoting brands. The adaptation of the offered products to the customer's needs is also of particular value. Different groups and segments of customers have different needs, which is most illustrated by the gender criterion - both women and men often have a completely different worldview and attitude to different areas of life, including shopping choices. Dynamic social changes and the strengthening position of women mean that brands have to adapt their marketing activities to their needs and expectations to a greater extent. That is why femvertising is becoming more and more popular every year - a communication trend that takes into account social dynamics, supports gender equality and is based on an understanding of the feminist perspective.
Keywords: femvertising; social media; communication; consumers; feminism